ALAT PEMANTAU KENDARAAN BERBASIS GPS DENGAN FITUR LOKAL DAN SMS PINTAR - Wibowo, Teguh (SENATIK STT Adisutjipto, 2013)
Nowadays, the development of the automotive industry in Indonesia is increasing followed by high number of motor vehicle theft. In order to reduce the motor vehicle theft case, a Global Positioning System (GPS) based instrument in motor vehicle is investigated to monitor the location of vehicles. This instrument will be run if there are a phone signal from provider and GPS signal from satellite. The method is that the owner sends a text to the destination number installed in the instrument. There are some codes needed to be paired to the instrument. If the code is matched, instrument will reply the text automatically based on the program installed in the instrument. This instrument has many advantages, such as could give the location accurately with an error less than 5 meters, could turn off the vehicle, could give an information if the vehicle is stolen, and also could record the conversations while the vehicles are in use. This instrument is also improved by installing the local language (Indonesian) and features which meet the owner requirements. Generally, it could be concluded that this instrument really helps the rider or owner from motor vehicle theft. Good response and accurate location given by the instrument verified by the finding of lost vehicle showed that this instrument could be applied and important if it is applied in the motor vehicles.